Reporting of ethics in peer-reviewed verbal autopsy studies: a systematic review. (30th October 2017) - Joshi, Rohina; Faruqui, Neha; Nagarajan, Shilpa R; Rampatige, Rasika; Martiniuk, Alex; Gouda, Hebe
Abstract: Introduction: Verbal autopsy (VA) is a method that determines the cause of death by interviewing a relative of the deceased about the events occurring before the death, in regions where medical certification of cause of death is incomplete. This paper aims to review the ethical standards reported in peer-reviewed VA studies. Methods: A systematic review of Medline and Ovid was conducted by two independent researchers. Data were extracted and analysed for articles based on three key areas: Institutional Review Board (IRB) clearance and consenting process; data collection and management procedures, including: time between death and interview; training and education of interviewer, confidentiality of data and data security; and declarations of funding and conflict of interest. Results: The review identified 802 articles, of which 288 were included. The review found that 48% all the studies reported having IRB clearance or obtaining consent of participants. The interviewer training and education levels were reported in 62% and 21% of the articles, respectively. Confidentiality of data was reported for 14% of all studies, 18% did not report the type of respondent interviewed and 51% reported time between death and the interview for the VA. Data security was reported in 8% of all studies. Funding was declared in 63% of all studies and conflict of interest in 42%. Reporting of all these variables increased over time. Conclusions: The results of this systematic review show that although there has been an increase in ethical reporting for VA studies, there still remains a large gap in reporting.